Determination of HIF1Ars11549465 Polymorphism in Elite Skiers - Canan Sercan; Korkut Ulucan; Fatih Bilici; Ömer Kaynar (Türk Spor ve Egzersiz Dergisi)
ABSTRACTStudies in sport genetics have increased nowadays and the identification of genotype and allelic distributions of candidate genes in different athletes has provided important information to sports scientists. One of the candidate genes studied in sports genetics is the hypoxia-inducible factor 1-alpha (HIF1A) gene, which is associated with the endurance phenotype. In our study, we aimed to determine the genotypic and allelic distribution of HIF1A rs11549465 polymorphism in Turkish Elite Ski Runners. 34 (23 male, 11 female) athletes were included in the study, and 1 cc of blood samples taken for routine analysis after the approval of the ethics committee was used for DNA isolation. The commercial kit was used for DNA isolation and genotyping was performed by Real-time PCR method. The number and percentage of CC, CT and TT genotypes of the HIF1A rs11549465 polymorphism were 24 (72.72%), 8 (24.24%) and 1 (3.03), respectively. In male skiers CC, CT and TT genotype numbers and percentages were determined as 17 (55.51%), 4 (12.12%) and 1 (3.03%) respectively. In female, CC and TT genotypes were determined as 7 (21.21%) and 4 (12.12%). We detected no TT genotype in female athletes. When we look at allel numbers, C allele was determined as 56 (84.84%) and T allele was determined as 10 (15.15%). This is the first study on HIF1A rs11549465 polymorphism on Turkish elite ski runners. The higher prevalence of CC genotype and C allele in the athlete group is similar to the previous studies on different groups of athletes. We believe that this study will be an important reference for further studies.